Finite Element Method Analysis in Simulation of Induction Heater Using Helical Coil Method - Lenny Iryani; Adolf S (Department of Mechanical Engineering, Universitas Andalas, 2023)
The problem of corrosion is very common in aircraft structure. This phenomenon is happened because of the two different types of material are in contact under moist or water. Along the operational hours of the aircraft structure, this corrosion is identified during the maintenance activity. To study about the corrosion removal by using the helical coil method, in this research the simulation of the removal corrosion in bolt and nut joint are conducted. The aim of the analysis i.e., to get the optimum electric current and frequency for induction heaters to heat stainless steel nuts that cannot be open, or the threads are stuck. The study was carried out so that the stainless-steel nuts reached a temperature of 400°C in one minute. Several variations of the electric current are carried out with magnitudes, namely 30 A, 40 A, 50 A and frequency variations of 300 kHz, 400 kHz, 500 kHz. Based on the variation of the electric current and frequency, the optimal electric current and frequency is generated to heat a stainless-steel nut that cannot be opened, or the screw is stuck at 50 A and 500 kHz with a temperature of 394°C in one minute.